PENGEMBALIAN KERUGIAN KEUANGAN NEGARA PADA SAAT PROSES PENYIDIKAN DAN KAITAN PELAKSANAAN PUTUSAN HAKIM (Studi Putusan Nomor 35/Pid.Sus/TPK/2015/PN.Mdn) - Immanuel Simanjuntak; Alvi Syahrin; Bismar Nasution; Mahmud Mulyadi (USU LAW JOURNAL, 2018)
ABSTRACT Indemnification of state financial in consequence of corruption is a law enforcement system that requires a process of negation of rights to assets the perpetrator of the State, the victims in a way done by way of confiscation, freezing, confiscation well within the competence of local, regional and international levels so that the wealth can be returned to the state ( victims) are legitimate.   Keywords: Returns Losses State Finance Investigation Process, Execution Judge Decision